Point of view as a category profiling the image of the city in Memoirs by Maria Kietlińska - Hawrysz, Magdalena; Kotlarska, Irmina (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The purpose of the sketch is to identify the sender’s point of view and to reconstruct the city profiles defined by his prism (understood from the social perspective as residents, events they participate in, everyday experiences, way of thinking and experiencing the world) revealed in Maria Kietlińska’s 19th-century diary, Memoirs. The analysis revealed a clear point of view — it is the view of an aristocrat who wrote in a mature age, whose youth fell during the time of national captivity, and whose memoirs are written during the difficult post-war situation. Such optics allowed to distinguish three profiles of old Krakow: sentimental, for which the most important thing is the dissonance between the brilliant past and the disappointing present, national, in which patriotism plays an important role, and the salon one, showing family ties and customs of the nineteenth-century elite